Dr. Eduardo Deveza won the Most Outstanding Educator Award for 1987 in an annual activity - Deveza, Eduardo (Animo Repository, 1987)
Dr. Eduardo Deveza, former head of the DLSU Faculty Association and faculty member of the Languages Department, won the Most Outstanding Educator Award for 1987 in an annual activity sponsored by Metrobank. He was one of the ten candidates from all over the Philippines to compete in the Metrobank Foundation search for top educators.